The stars are fire [compact disc, unabridged] - Shreve, Anita (Random House Audio, 2017)
In October 1947, after a summer long drought, fires break out all along the Maine coast from Bar Harbor to Kittery and are soon racing out of control from town to village. Five months pregnant, Grace Holland is left alone to protect her two toddlers when her husband, Gene, joins the volunteer firefighters. Along with her best friend, Rosie, and Rosie's two young children, Grace watches helplessly as their houses burn to the ground, the flames finally forcing them all into the ocean as a last resort. The women spend the night frantically protecting their children, and in the morning find their lives forever changed: homeless, penniless, awaiting news of their husbands' fate, and left to face an uncertain future in a town that no longer exists.